Theory and Behavior of Multiple Unit Discriminative Auctions - COX, JAMES C.; SMITH, VERNON L.; WALKER, JAMES M. (Journal of Finance, 1984)
ABSTRACT This paper reports the results of controlled experiments designed to test the Harris‐Raviv generalization of the Vickrey theory of bidding in multiple unit discriminative auctions. The paper also discusses further development of the theory—in a way suggested by the experimental results—to include bidders with distinct risk preferences.